Shared Decision Making and Choice for Elective Surgical Care: A Systematic Review. (March 2016) - Boss, Emily F.; Mehta, Nishchay; Nagarajan, Neeraja; Links, Anne; Benke, James R.; Berger, Zackary; Espinel, Ali; Meier, Jeremy; Lipstein, Ellen A.
Objective: Shared decision making (SDM), an integrative patient-provider communication process emphasizing discussion of scientific evidence and patient/family values, may improve quality care delivery, promote evidence-based practice, and reduce overuse of surgical care. Little is known, however, regarding SDM in elective surgical practice. The purpose of this systematic review is to synthesize findings of studies evaluating use and outcomes of SDM in elective surgery. Data Sources: PubMed, Cochrane CENTRAL, EMBASE, CINAHL, and SCOPUS electronic databases. Review Methods: We searched for English-language studies (January 1, 1990, to August 9, 2015) evaluating use of SDM in elective surgical care where choice for surgery could be ascertained. Identified studies were independently screened by 2 reviewers in stages of title/abstract and full-text review. We abstracted data related to population, study design, clinical dilemma, use of SDM, outcomes, treatment choice, and bias. Results: Of 10, 929 identified articles, 24 met inclusion criteria. The most common area studied was spine (7 of 24), followed by joint (5 of 24) and gynecologic surgery (4 of 24). Twenty studies used decision aids or support tools, including modalities that were multimedia/video (13 of 20), written (3 of 20), or personal coaching (4 of 20). Effect of SDM on preference for surgery was mixed across studies, showing a decrease in surgery (9 of 24), no difference (8 of 24), or an increase (1 of 24). SDM tended to improve decision quality (3 of 3) as well as knowledge or preparation (4 of 6) while decreasing decision conflict (4 of 6). Conclusion: SDM reduces decision conflict and improves decision quality for patients making choices about elective surgery. While net findings show that SDM may influence patients to choose surgery less often, the impact of SDM on surgical utilization cannot be clearly ascertained.